Determining Vehicle Speed from Dashcam Audio Analysis - A. A. Godlevskii (Теория и практика судебной экспертизы)
The article offers a method for determining vehicle speed from the audio track recorded by the dashboard camera mounted on the car in question. The author analyzed the operation of a four-stroke internal combustion engine, and established a dependency between the number of rotations (rpm) of the engine crankshaft and the number of rotations transferred to the wheel by the manual transmission. The author presents a formula that helps to determine the static radius of the wheel from its marking symbols on the tire. He looks at examples from forensic casework and offers options for determining the ID number of an engaged gearbox. Furthermore, he reviews the possibilities of applying this method to vehicles with an automatic transmission. In conclusion, the article presents the results of tests of the proposed method conducted by leading experts from various forensic institutions of the Russian Ministry of Justice. They point to the consistency of results when engine rpm is calculated based on cepstral analysis and engine tachometer readings.